Introduction: Promoting Justice Through Interdisciplinary Teaching, Practice, and Scholarship - Karen Tokarz (Washington University Journal of Law & Policy, 2003)
Professionals across a wide range of fields have increasingly recognized the benefits of interdisciplinary teaching, practice, and scholarship. Educational institutions, especially law schools, have responded by developing clinical courses and other types of courses in a variety of subject areas, using a range of interdisciplinary approaches. Yet, there has been little focused discussion concerning the goals of these collaborative enterprises, how best to structure these efforts to achieve their intended objectives, and the potential impact on each discipline’s ethical obligations. The working conference, as well as the pre and post-conference volumes of the Journal, will address the following issues: What do we mean by “interdisciplinary” and “multidisciplinary,” and is there a meaningful difference? How does one go about discerning the goals of collaborations between disciplines? What can we learn from reports from the field as to what are the best practices, different models, and likely problems? In what ways does the clinical teaching model, with its goals of educating students, providing services to the community, and advancing justice, serve as a model? How does one go about designing and developing an interdisciplinary program or class? What are the common ethical issues that arise in interdisciplinary education and practice, and what are some guidelines for resolving them? What are some of the challenges to interdisciplinary teaching, practice, and scholarship?
Keywords: Interdisciplinary approach in education; Law schools; Multidisciplinary practices